High-temperature tribological performance of Co45Fe20Cr15W15Si5 complex concentrated alloy: Evolution of multiscale microstructure and friction-induced in-situ oxide layer - Jiang, Junjie; Xin, Benbin; Zhang, Aijun; Han, Jiesheng; Yu, Qiangliang; Meng, Junhu (Journal of materials research and technology, 2025)
Designing wear-resistant alloys for extreme high-temperature tribological conditions remains challenging due to the conflicting requirements between oxidation resistance and mechanical stability. The high temperature wear behavior of these materials is significantly affected by microstructure transformation and friction-induced oxide layer evolution. Herein, a Co45Fe20Cr15W15Si5 complex concentrated alloy (CCA) which composed by FCC and multi-scale silicides was developed by vacuum arc melting. This alloy exhibits good high temperature wear resistance (the wear rate <4.5 × 10−7 mm3 N−1 m−1), which is mainly due to the multiscale structure and friction-induced in-situ oxide layer. Multiscale silicides can effectively enable the alloy to resist abrasive wear and better relieve stress. The friction-induced in-situ layered oxide layer leads to a soft-hard combined dual-layer oxide structure, which can prevent further oxidation while providing good lubricity.